2018
DOI: 10.1111/jcal.12283
|View full text |Cite
|
Sign up to set email alerts
|

Teacher practices during Year 4 of a one‐to‐one mobile learning initiative

Abstract: This study examines the ways in which all nine middle school teachers in a private school for boys in the United States integrated mobile devices with content and pedagogy 4 years into the implementation of a one-to-one initiative. It also examines teacher perceptions of the benefits and challenges related to the implementation of mobile devices in real classroom contexts. Data were collected from multiple sources including teacher lesson plans, classroom observations, and interviews. Data collection and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Findings from the current research indicate that extensive reading, backed-up with purposeful e-learning games, digital stories, and activities offered in the Jolly Phonics application, were effective for building students' phoneme blending and segmenting skills. The findings verify studies of researchers (Aleven et al, 2016;Cullata et al, 2022;Gee, 2018;Reichert & Mouza, 2018;Vanden et al 2021;Vega, 2016;Wei et al, 2018;Zugarramurdi et al, 2022) who highlighted that children benefit from the Jolly Phonics Lessons application's interactive features, aside from intensive independent practice, contributes in the development of the blending and segmenting competencies.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings from the current research indicate that extensive reading, backed-up with purposeful e-learning games, digital stories, and activities offered in the Jolly Phonics application, were effective for building students' phoneme blending and segmenting skills. The findings verify studies of researchers (Aleven et al, 2016;Cullata et al, 2022;Gee, 2018;Reichert & Mouza, 2018;Vanden et al 2021;Vega, 2016;Wei et al, 2018;Zugarramurdi et al, 2022) who highlighted that children benefit from the Jolly Phonics Lessons application's interactive features, aside from intensive independent practice, contributes in the development of the blending and segmenting competencies.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…The incorporated games in the application about blending sounds contributed on their of understanding the sound that the letters represent and be able to blend those sounds to create words. The findings underpin the studies of Aleven et al (2016) who mentioned that adaptive learning technology can to significantly better gains in letter-blending skills among young students, and Reichert and Mouza (2018) who indicated that digital technology can be highly effective in helping students, especially with hearing challenges, improve their phoneme blending skills As presented in Tables 7 and 8, phoneme blending skill levels were identified based on the mean score interpretation table. Both groups got low pretest mean scores implying that students were in the novice stage of phoneme blending skills.…”
Section: The Effects Of Integrating Jolly Phonics Lessons Application...mentioning
confidence: 56%
“…More relevant studies in the domain of education (Kasurinen & Knutas, 2018;Koivisto & Hamari, 2019;Seaborn & Fels, 2015) identify the need for more advanced classroom technology that adapts to modern students' needs (Montazami et al, 2022;Young, 2016). Further, technology should be fit for purpose; otherwise, students may misuse the technology or may be distracted (Miller, 2012;Reichert & Mouza, 2018). The SRS provides a distinct advantage as a fit-for-purpose teaching tool which offers little opportunity for distraction, but studies using SRS have to date been conducted primarily on University students (Çelik & Baran, 2021;Benson et al, 2017;Pearson, 2017).…”
Section: Strategies In Gamified Experiential Technologymentioning
confidence: 99%
“…This is an open access article distributed under the CC BY-NC 4.0 license -http://creativecommons.org/licenses/by-nc/4.0/. Reichert & Mouza (2018) investigated the benefits and challenges related to the implementation of mobile devices in real classroom contexts in a private school in USA. Moreover, Colwell & Hutchinson (2015) reported that the use of digital technology supports literacy instruction and development in the following ways: (a) Students wrote for more authentic purposes; (b) inclusion of oral language activities using digital recording devices supported students' idea development and writing; (c) students had increased opportunities to interact and collaborate with peers, critically evaluate each other' work, and consider multiple perspectives; (d) students were encouraged to think about traditional content in new ways; and (e) digital tools provided insight into students' reading behaviours and comprehension.…”
Section: Advances In Social Science Education and Humanities Research Volume 546mentioning
confidence: 99%